2012
DOI: 10.1007/s00467-012-2236-3
|View full text |Cite
|
Sign up to set email alerts
|

Why multidisciplinary clinics should be the standard for treating chronic kidney disease

Abstract: In adults, strong evidence indicates that slowing progression of chronic kidney disease (CKD) requires an integrated, multidisciplinary approach. In children, however, this approach has not been studied. This editorial commentary to the study by Ajarmeh et al in this volume of Pediatric Nephrology highlights how a dedicated, multidisciplinary team of physicians, nurses, pharmacists, dieticians, social workders and clinic data managers slowed the progression of CKD in children to a remarkable degree. We discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
(22 reference statements)
0
17
0
3
Order By: Relevance
“…Estimates indicate that the additional salary costs of the multidisciplinary team (pharmacist, nurse, social worker, dietitian, data manager) could be recovered in one year if dialysis were delayed by one year in only 2% of pediatric patients [15]. …”
Section: Models That Incorporate Pharmacist Care and Payment Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates indicate that the additional salary costs of the multidisciplinary team (pharmacist, nurse, social worker, dietitian, data manager) could be recovered in one year if dialysis were delayed by one year in only 2% of pediatric patients [15]. …”
Section: Models That Incorporate Pharmacist Care and Payment Mechanismsmentioning
confidence: 99%
“…One large cross-sectional study observed associations between uncontrolled hypertension and CKD patients with greater medication nonadherence [14]. However, the greatest potential for reducing future morbidity and costs for end-stage renal disease (ESRD) care is to reduce the rate of kidney disease progression and incident ESRD cases [15]. Accordingly, this review discusses reasons for gaps in medication-related care for CKD patients, pharmacy services to reduce these gaps, and successful models that incorporate pharmacist care and reduce MPRs.…”
Section: Introductionmentioning
confidence: 99%
“…Es aquí donde la enfermera se convierte en el punto articulador de la intervención, además quien hace la búsqueda activa de niños ante problemas de cumplimiento. Se conoce que un equipo multidisciplinario en niños y adolescentes con IRC puede retrasar la progresión de la disfunción renal a un grado notable (15,16) . La participación en la investigación no fue obligatoria, por lo cual se presentó un consentimiento informado y asentimiento, en el cual se informó por escrito la participación voluntaria en el proyecto y el derecho que tenía el Cuidador a retirarse en el momento que lo decidiera.…”
Section: Nº 34 Abril 2014unclassified
“…Tal como sugería la experiencia, y algunos estudios previos (15,16) observamos que la participación de los cuidadores primarios, la orientación del equipo multidisciplinario, en especial del Profesional de Enfermería quien es el que realiza el cuidado extramural es relevante para optimizar la adherencia en el tratamiento, el reconocimiento de factores de riesgo y la realización correcta de la DPA en casa. En esta investigación pudimos ratificar lo anterior, por medio de la aplicación del formato de vista domiciliaria, con el cual exploramos de forma clara y sencilla los aspectos más puntuales del procedimiento de DPA en casa, del mismo modo facilita la comunicación de la familia con el equipo de salud, acercándolos más a las recomendaciones y educación, esto se logró con base al entrenamiento y evaluación que se hace por dos semanas al CP (Cuidador primario) en la unidad renal previo a la DPA.…”
Section: Discusionunclassified
See 1 more Smart Citation